Deteksi Titik Api Terpusat Menggunakan Kamera Dengan Notifikasi Berbasis Sms Gateway Pada Raspberry Pi - Syahrul Yoga Pradana; Fitri Utaminingrum; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Fire accident is an event that produce flame, in which fire accident could make a significant loss and even casualty. Fire accident mostly caused by human error. This research conducted to create a system for flame detection utilizing camera (2 camera) attached in every room inside a home in order to facilitate user to detect flame as soon as possible when the fire started in each of the room, and also made an advantage from Gateway SMS as a notifier alert. This system utilized a Mini PC (Raspberry Pi 3 Model B) acted as a data processor and control system. And also, this system completed by using Logitech C525 Camera acted as an input to take flame image. As for the Buzzer, it rings the alarm dan Modul SIM900A acted as an output to notify by SMS when there is flame. This system used image processing method processed inside Raspberry Pi 3 Model B doing some controls over the output income which is by doing Morphological Image Filtering through OpenCV. Result obtained for flame detection accuracy was 90%, as for flame detection inter-camera in every room was 96.66%, and the computation mean time tests were 27.5ms, 22.2ms, and 36.25ms